Dekoracje fasad gdańskich kamienic przypisywane Andrzejowi Schlüterowi Młodszemu - Lipska, Dąbrówka (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
The popularity of and general recognition for the talent of this court builder of Frederick I, King in Prussia was one of the reasons for numerous publications devoted to the life and works of Andreas Schluter, the Younger, related mainly to the late – Berlin works – leaving his early works in oblivion. This paper is dedicated to the Gdańsk monuments attributed to Andreas Schluter, the Younger and especially to two tenement houses (located at Długi Targ 3 and 20), whose facade decoration has been attributed to the sculptor for years. Their history (including the postwar restoration), iconography and form were analyzed, which has enabled one to put forward a hypothesis about the origin of the patterns for the facade decoration, which stood out above the Gdańsk residential building in this period. They were presented in a wider context of decorations of the 17th century tenement houses in Poland and Germany, and the details were compared to the preserved works of Andreas Schluter. Unfortunately, detailed archive search query did not answer the following questions: are these the works of the master? However, on the basis of the analysis of iconography and decoration forms, it is hightly doubtful whether the facade of the tenement house at Długi Targ 3 was his work.